Governance, Markets and Institutions: Russia and Germany Compared - Marina Spirina (Journal of Economic Sociology, 2015)
The Summer School “Governance, Markets and Institutions: Russia and Germany Compared” was held from September 27 to October 10, 2015 under the coordination of the Institute for East European Studies, Free University of Berlin (Berlin) with the participation of Hertie School of Governance (Berlin), German Institute for Economic Research (Berlin), Higher School of Economics (Moscow) and European University at St. Petersburg (St. Petersburg). The Volkswagen Foundation (Volkswagen Stiftung) provided the Summer School with necessary financial support. Around thirty doctoral students and postdoctoral scholars (both EU and non-EU) from a variety of disciplines including sociology, political science, economics, social anthropology, law, history and geography took part in this academic event. In addition, eight Russian MA students from social and political sciences were admitted as participants with special support from the Higher School of Economics.The keynote speakers and lecturers from the Higher School of Economics (Moscow) were Alexander Chepurenko, Victoria Antonova, Fuad Aleskerov, Lilli DiPuppo, Andrei Melville, Yuval Weber, Andrei Yakovlev, Vladimir Zuev, Alexey Zakharov and Christopher Gerry. Nikita Lomagin presented his research on behalf of the European University at St. Petersburg (St. Petersburg). Among the participants from the Free University of Berlin (Berlin) were Katharina Bluhm, Carsten Schröder, Sabine Kropp, Tanja Börzel, Klaus Hoffmann-Holland, Philipp Engler, Klaus Segbers and Aron Buzogany. A number of scientists and researchers from other universities also took part in this academic event, including Klaus Desmet (Southern Methodist University, Texas), Volker Schneider (University of Konstanz, Konstanz), Nikolaus Wolf (Humboldt University, Berlin), Panu Poutvaara (Ludwig Maximilian University of Munich, Munich), David Woodruff (London School of Economics and Political Science, London).